Protective Effect of Tomato By-Product in Refined Sunflower Oil with Different Lipid Profiles - Idoya Fernández-Pan; Sandra Horvitz; Francisco C. Ibañez; Paloma Vírseda; María José Beriain (Molecules)
The recovery of carotenoids, particularly lycopene, from industrial tomato by-products is contingent upon the composition of the raw material, the harvesting season, and the specifics of the extraction process. Industrial tomato by-product from three harvest seasons (S1, S2, and S3) was revalorized and used as a lycopene natural source. Pressurization-assisted extraction of lycopene was carried out using two types of refined sunflower oil (high oleic, HO, and low oleic, LO). The carotenoid and tocopherol content, as well as the fatty acid profile, were analyzed in the resulting HO and LO oil samples, and thermooxidation stability was evaluated. Lycopene recovery was found to be higher in the LO oil than in the HO oil using the by-product from the S3 harvest. Conversely, the tocopherol content declined in both oil types following the incorporation of the S3 by-products. The addition of by-products did not affect the thermooxidation stability of the HO oil. Conversely, the thermooxidation stability of the LO oil increased by about 3.2 ± 0.6 h, irrespective of the season. The findings of this study demonstrate that the addition of tomato by-product, regardless of its lycopene content, provides a protective effect against the thermooxidation of conventional sunflower oil.